CORRELATION OF FINANCIAL STATEMENT COMPONENTS IN DETECTING FINANCIAL FRAUD - Handayani Handayani; Tarjo Tarjo; Yuni Rimawati (Asia Pacific Fraud Journal, 2016)
The purpose of this study is to determine the absence of correlation offinancial statement components as red flags in detecting financial statement fraud. The sampling in this study is done using purposive sampling technique. There are two categories of companies used as the study sample:fraud companies and non-fraud companies. Fraud companies are the companies that get sanction from Capital Market Supervisory Agency (Bapepam) andFinancial Services Authority (OJK) period 2000-2014, while non-fraud companies are selected with the criteria: having equivalent assets, engaging in the same industry, and using the same financial statements as the financial statements used by the fraud companies. The total samples of this study are 122 companies consisting of 61 fraud companies and 61 non-fraud companies. Spearman correlation test is used to answer the research hypothesis.The conclusions of this study are (1) the absence of correlation between cash flows andearnings can be usedas red flags to detect fraud, (2) the existence of correlation between receivables and revenues cannot be used as red flags to detect fraud, (3) the existence of correlation between allowances for uncollectible accounts and receivable cannot be used as red flags to detect fraud.